Populist attitudes and the populist radical right vote in different types of elections: evidence from Portugal - Santana Pereira, José (2024)
In this article, the impact of populist attitudes on the vote for the populist radical right is assessed in the context of first- and second-order elections, under the expectation that the effect of populist attitudes will be stronger in the latter. To test this assumption, the focus is placed on the case of Portugal, and original survey data collected in 2021 – including information on vote choice in the January presidential elections, vote intentions in hypothetical legislative elections, populist attitudes and relevant controls – is used. The results show that populist attitudes increased the odds of voting for André Ventura in the presidential election but had no impact on the probability of expressing an intention to vote for Chega in legislative elections. The implications of these patterns are discussed.